THE EFFECTIVENESS OF SCAFFOLDING METHOD IN ENHANCING ARABIC LANGUAGE LEARNING OUTCOMES: A QUASI-EXPERIMENTAL STUDY OF GRADE VII STUDENTS - Marhamah Ulfa; Triana Susanti; Edi Suyanto (CV. Bunda Ratu, 2026)
This study investigates the effectiveness of the scaffolding method in improving Arabic language learning outcomes among seventh-grade students at MTsN 1 Bengkalis. Using a quantitative quasi-experimental approach with a one-group pretest-posttest design, the research examined 30 students selected through random sampling from nine seventh-grade classes. Data collection comprised pretest and posttest scores alongside validity and reliability testing of assessment instruments. Results of the paired t-test analysis (t = -10.537, df = 17, p = 0.000) demonstrated statistically significant improvement in Arabic learning outcomes after implementing the scaffolding instructional method. The mean score increased from 66.33 (SD = 13.564) to 79.66 (SD = 8.822), representing a mean difference of 13.33 points. The Cronbach's alpha coefficient (α = 0.864) confirmed acceptable internal reliability of the assessment instruments. These findings suggest that scaffolding, as operationalized through structured teacher guidance aligned with students' Zone of Proximal Development (ZPD), constitutes an effective pedagogical intervention for enhancing Arabic language proficiency in Islamic secondary education contexts. The study underscores the importance of providing calibrated instructional support that diminishes as student competence increases, thereby supporting autonomous language learning development.